Impact of Institutional Trust on Financial Inclusion: Evidence from Gandaki Province, Nepal (Quest Journal of Management and Social Sciences, 2025)
Background: Financial inclusion is essential for economic development, yet many people in Nepal remain excluded from formal financial services. Institutional trust has been identified as a key factor influencing individuals' willingness to engage w ith financial systems. People who trust financial institutions are more likely to open accounts, take loans, and use other financial services. Trust can significantly impact these services' access, availability, and usage in regions like Gandaki Province. This study investigates the role of institutional trust in promoting financial inclusion and aims to provide insights for policymakers and financial institutions.Purpose: Institutional trust significantly influences individuals' willingness to use formal financial services. It directly influences their willingness to open accounts, take loans, and use other financial services. The study aims to evaluate the impact of institutional trust on financial inclusion in Gandaki province, Nepal.Methods: This study employed descriptive as well as analytical research designs. A total of 600 households were selected using a multistage sampling technique. First, Gandaki province was purposively selected. In the second stage, three districts – Kaski, Syangja, and Parbat- were randomly chosen, and households from these districts were selected proportionately. Finally, one chief household decision-maker was conveniently chosen as the respondent. The data collection process involved face-to-face interviews using a researcher-developed survey schedule. For data analysis, percentage analysis, exploratory factor analysis (EFA), and structural equation modelling (SEM) were employed.Finding: The results revealed that institutional trust positively and significantly influences financial inclusion. It also found that institutional trust positively and significantly affects the accessibility, availability, and usage dimensions of financial inclusion in Gandaki Province, Nepal.Conclusion: This study concluded that individuals with a higher level of trust are more likely to access, avail, and utilise financial services, suggesting that fostering trust is crucial for promoting financial inclusion.Keywords: Exploratory Factor Analysis, Financial Services, Nepal, Structural Equation Modelling, Trust in Financial InstitutionsJEL Codes: C38, G21, C39